2018
DOI: 10.3390/fluids3020027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Non-Stationarity of Rainfall Events on the Design of Hydraulic Structures for Runoff Management and Its Applications to a Case Study at Gordo Creek Watershed in Cartagena de Indias, Colombia

Abstract: Abstract:The 24-h maximum rainfall (P 24h-max ) observations recorded at the synoptic weather station of Rafael Núñez airport (Cartagena de Indias, Colombia) were analyzed, and a linear increasing trend over time was identified. It was also noticed that the occurrence of the rainfall value (over the years of record) for a return period of 10 years under stationary conditions (148.1 mm) increased, which evidences a change in rainfall patterns. In these cases, the typical stationary frequency analysis is unable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
(37 reference statements)
0
12
1
Order By: Relevance
“…Overall, the Gumbel distribution was the best fit in 63.2% of the 19 rain gauges analyzed, while GEV was the best fit in only 36.8%. These results represent a shift from the findings by González-Álvarez et al [45], where GEV was best in 53.8% of the 13 rain gauges assessed. This is due to the fact that the Gumbel distribution was the best CDF among the new additional six rain gauges analyzed in this study.…”
Section: Identification and Delimitation Of Homogeneous Regionscontrasting
confidence: 65%
See 1 more Smart Citation
“…Overall, the Gumbel distribution was the best fit in 63.2% of the 19 rain gauges analyzed, while GEV was the best fit in only 36.8%. These results represent a shift from the findings by González-Álvarez et al [45], where GEV was best in 53.8% of the 13 rain gauges assessed. This is due to the fact that the Gumbel distribution was the best CDF among the new additional six rain gauges analyzed in this study.…”
Section: Identification and Delimitation Of Homogeneous Regionscontrasting
confidence: 65%
“…The non-stationary frequency analysis was performed according to the methodology proposed by Obeysekera and Salas [1,43,44], which uses (a) the GEV function by varying the location parameter over time and maintaining the constant parameters of scale and shape (called GEVmu), and (b) a definition of the return period (Tr) according to the geometric distribution given by Equation (20), where Pj is the is the time-varying exceedance probability, and j represents the year to be projected [1,45]. The GEVmu function was already tested by Gonzalez-Alvarez et al [45] in the Colombian Caribbean region, where a sensitivity analysis showed that varying the shape and/or scale parameters did not bring any improvement in the performance of either GEV or Gumbel distributions.…”
Section: Stationary and Non-stationary Rainfall Frequency Analysismentioning
confidence: 99%
“…Scatter plots of the multiannual series of P 24h-max of each rain gauge revealed that there might be regionalization of the daily maximum rainfall trends within the departments that need to be further explored and analyzed, as it was observed that rainfall observations showed a noticeable increasing or decreasing trend line over time, which may indicate (a) a change in the rainfall pattern due to, among others, anthropogenic factors and (b) that a non-stationary frequency analysis is more suitable for the rainfall data of those rain gauges at a local level [66,67]. Figure 3 shows the scatter plot and the trend lines of the rain gauges Puerto Giraldo and Los Campanos located in the department of Atlántico.…”
Section: Multiannual Time Series Of P 24h-max Valuesmentioning
confidence: 99%
“…In recent years, due to the influence of global warming as well as changes in the magnitude and patterns of extreme precipitation events, it is necessary to periodically update the magnitudes of the maximum rainfall that are used to design hydraulic works [7]. In particular, extreme weather events such as floods, droughts and storms can increase in frequency over time [8][9][10]; thus, it is necessary to determine probability functions that best represent current trends in the data.…”
Section: Introductionmentioning
confidence: 99%